Survival probability during one-year follow-up after index hospitalization for heart failure: an Italian retrospective study - Romano, S.; Dante, A.; Mammarella, L.; Masotta, V.; Petrucci, C.; Lancia, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Heart failure affects about 64 million people worldwide, and despite the economic resources employed to improve its prognosis, mortality is still alarming. The aim of this study was to investigate the impact of patients’ characteristics on survival probability during one-year follow-up after an index hospitalization for heart failure. Study design. A three-year retrospective study was conducted on the records of the Hospitals belonging the Local Health Unit of L’Aquila, a Healthcare Facility located in the centre of Italy. Methods. Patients admitted to hospital with a heart failure event as main diagnosis were selected and followed up for one year after their discharge to obtain data for survival analysis. Results. During the observational period for 1,929 patients hospitalized with a Heart failure index event, 1,655 (85.8%) of them were discharged alive and followed up for one year after the discharge. Fourteen percent of patients (n = 232) died for reasons related to Heart failure during the follow-up period. Fifty percent of them (n = 116), died within three months from the index hospitalization discharge. Age ≥75 years (HR 3.192, 95% CI 1.964–5.188), discharging to home (HR 0.399, 95% CI 0.297–0.536), length of stay ≥8 days during the index hospitalization (HR 1.533, 95% CI 1.163–2.019), and high education level (HR 0.517, 95% CI 0.273–0.977), were found to be associated with the survival probability. Conclusion. Study results indicate that older patients, especially those with a low educational level, those with longer index hospitalization, and those not sent directly to home, deserve more care and attention after discharge.